Ketidaklengkapan Imunisasi Dasar pada Bayi Selama Pandemi Covid-19 di Wilayah Kerja Puskemas Bandar Petalangan Kabupaten Pelalawan - Ilhamdsyah Harahap; Oktavia Dewi; Mitra Mitra (LPPM Hang Tuah Pekanbaru, 2023)
Achievement of complete basic immunization at Puskesmas bandar Petalangan was only 77.7%. There are various causes for the low achievement of Complete Basic Immunization such as remote and difficult to reach immunization service locations, irregular service schedules and incompatible with community activities, unavailability of immunization cards (MCH handbook), low public awareness and knowledge of benefits. The research objective was to know the timeliness of the implementation of basic immunization in infants during the Covid-19 pandemic in the work area of the Bandar Petalangan Community Health Center, Pelalawan Regency in 2020. The research method used a cross sectional design with a population of mothers who had babies aged 3-12 months, totaling 257 people with a sample. totaled 161 people. The sampling technique used accidental sampling. Data analysis was performed using univariate, bivariate and multivariate multiple logistic regression. The results showed that there were 54 mothers (33.5%) who were not on time in basic immunization, variables related to the timeliness of basic immunizations were maternal education (POR = 2.9), affordability of immunization sites (POR = 3.6) and family support (POR = 3.3). It is recommended that BLUD Puskesmas bandar Petalangan be able to increase and equalize posyandu service facilities, increase information and education communication (KIE) efforts to mothers and families about the importance of basic immunization in infants and increase the role of volunteer health.